2021
DOI: 10.3389/fimmu.2021.667097
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effects of Gut Microbiome on Systemic Lupus Erythematosus: A Two-Sample Mendelian Randomization Study

Abstract: The observational association between gut microbiome and systemic lupus erythematosus (SLE) has been well documented. However, whether the association is causal remains unclear. The present study used publicly available genome-wide association study (GWAS) summary data to perform two-sample Mendelian randomization (MR), aiming to examine the causal links between gut microbiome and SLE. Two sets of MR analyses were conducted. A group of single nucleotide polymorphisms (SNPs) that less than the genome-wide stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 40 publications
0
102
0
5
Order By: Relevance
“…( 14 ) and Xiang et al. ( 15 ) performed MR analyses to investigate the effects of gut microbiota on IBD and SLE, respectively. Our study differs from their studies in the following three aspects: First, our study is more comprehensive in its investigation of ADs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 14 ) and Xiang et al. ( 15 ) performed MR analyses to investigate the effects of gut microbiota on IBD and SLE, respectively. Our study differs from their studies in the following three aspects: First, our study is more comprehensive in its investigation of ADs.…”
Section: Discussionmentioning
confidence: 99%
“…The above two studies fall short in that they treat gut microbiota composition as a whole without distinguishing specific taxa, while different microbial taxa may have distinct effects on human health. During the preparation of this article, Zhang et al (14) and Xiang et al (15) investigated the causal effects of specific microbial taxa on two ADs, inflammatory bowel disease (IBD) and SLE. However, studies on other ADs are still sparse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…R 2 denotes the exposure variance of the chosen SNPs interpretation, n is the sample size, and K represents the number of instrumental variables included. If F is <10, there is a weak relationship between the IVs and exposure ( 26 ); that they are unrelated to confounding factors (independence assumption); and that they influence the outcome solely through their effects on the exposure of interest (exclusion restriction assumption), implying that there is no horizontal pleiotropic effect between IV and outcomes ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep duration can also affect the functional correlation of intestinal microbiota and its metabolic integrity (10). In addition, a recent Mendelian randomization (MR) analysis showed that intestinal microbial components had a causal impact on the risk of SLE (11). Therefore, sleep may have an impact on SLE pathogenesis through gut microbes.…”
Section: Introductionmentioning
confidence: 99%